Analysing the existing Malaysian Government Policies related to developing Waqf Land for Agriculture - Ishak , Amal Hayati; Yahaya , Muhamad Hasif; Jamaluddin , Hanif; Abd Latib , Noor Aznaim (Environment-Behaviour Proceedings Journal, 2025)
In Islam, waqf is a religious deed. Donors entrusted their property to waqf trustees to receive eternal rewards. This situation necessitates active involvement from the government and relevant authorities to ensure waqf properties are developed efficiently and sustainably. Therefore, this article analyses the policies in Malaysia related to waqf land development for agriculture, reflecting the concerted effort in ensuring its sustainable benefit. Employing a content analysis approach, this study concludes on five categories of policies: physical infrastructure, governance and law, finance and accounting, and agriculture. The policies illustrate government’s recognition on development through waqf infrastructures and its capacity for socio-economic improvement.